The accumulation of foreign exchange by central banks: Fear of capital mobility? - Andreas Steiner (Osnabrück University, Institute of Empirical Economic Research, 2010)
Foreign exchange holdings by central banks have increased significantly in the recent past. This article explains this development as a result of the liberalization of international capital markets. First, central banks accumulate reserves in order to protect the economy from potentially detrimental effects of sudden stops of capital flows and flow reversals. Second, central banks use the accumulation of reserves as a substitute for capital controls. Changes in the level of reserves are a form to manage net capital inflows. They permit the central bank to preserve some leeway for an independent monetary and financial policy despite the classic policy trilemma. The empirical analysis of a large panel data set supports the hypothesis that the accumulation of reserves is the consequence of a fear of capital mobility suffered by central banks.
Keywords: E58; F31; 330; international reserves; capital mobility; macroeconomic trilemma